Elements of African Traditional Religion in Christ Apostolic Church, Southwestern Nigeria (2012)
The Christ Apostolic Church (CAC) has a reputation for high spiritualism, but it also has a subtle link with African traditional religion (ATR). Studies on the church have concentrated on the church’s origin, spiritual programmes and legendary personalities but have not addressed the church’s connection with .ATR This study, therefore examined the ATR elements appropriated in CAC in terms of the objects used, the procedures involved in their use and the functions associated with them. Sixty CAC branches were purposively selected in Ibadan, Lagos, Abeokuta, Akure, Ado-Ekiti and Osogbo. Unstructured interviews were conducted with purposively sampled 60 pastors (10 from each city) and 120 laity (20 from each city). A total of 360 copies of a questionnaire were administered to the same number of respondents. A ten-week participant observation monitoring was also conducted. Data were subjected to content analysis and simple descriptive analysis. Four ATR elements were adopted in CAC: spiritualisation of the head, pregnancy conception, photographs/objects and the earth. Across all these elements, water, olive oil and Psalms/songs were utilised, albeit differently. For the head, spiritual washing with water and consecration with olive oil occurred. For conception, consecrated water was drunk and rubbed on the tummy. Water was sprinkled on photographs, handkerchiefs, mantles, land and all forms of property. Barren women, carrying dummy/symbolic babies, sprinkled water or olive oil on their tummies while chanting psalms or songs spiritedly. Pregnant women prayed naked in the mid-night, chanting psalms and songs. Five types of chanting were identified: psalms/songs associated with warfare, imprecations, power, spiritual beings and supremacy of God. The ATR belief in the spiritualisation for destiny fulfilment was slightly modified in the CAC context where the head was believed to be spiritually empowered to accept its fortunes and reverse negative situations. In ATR and CAC, using spiritually treated water and chanting was believed to be capable of bringing about conception. While the spiritualisation of photographs/objects in ATR was done to manipulate situations positively or negatively, it was done in CAC for positive effects. The spiritualisation of the earth in ATR was to manage metaphysical forces, but it was used in CAC to spiritually influence blessings and protection. About seventy percent of the respondents believed that the head could harbour evil or good, and therefore needs to be spiritually treated while 88% believed that sanctified water and oil could cure ill-luck. About eighty percent believed that barrenness transcends medical reasons, and should be spiritually handled, 78.8% believed that praying on photographs/objects had positive effects, and 69.2% believed that evil and good forces are resident in the earth, and could be positively or negatively engaged. The appropriation of some natural and synthetic elements used in ATR in CAC shows a link between the church and the religion. Thus, the concepts of spiritual manipulation and protection enhancement are evident in the procedures of both ATR and CAC